Удосконалення теоретичної підготовленості тренерів, які спеціалізуються в одноборствах до використання сучасних фітнес-технологій у професійній діяльності - Хацаюк, О. В.; Khatsaiuk, O. V.; Шапаренко, І. Є.; Shaparenko, I. Ye.; Чередніченко, С. В.; Cherednichenko, S. V.; Драгунов, Д. М.; Drahunov, D. M.; Кулібаба, С. О.; Kulibaba, S. O.; Мазур, В. Й.; Mazur, V. Y. (Науковий часопис НПУ імені М. П. Драгоманова. Серія 15: Науково-педагогічні проблеми фізичної культури (фізична культура і спорт). - 2023. - Вип. 10(170). - С. 141-148, 2023)
Розроблено експериментальну програму формування теоретичних знань тренерів, які спеціалізуються в одноборствах у напрямі застосування ними сучасних фітнес-технологій у професійній діяльності. Запропоновану «експериментальну програму» планується реалізувати упродовж двох основних етапів: «Формуючого» та «Базового» із відповідним навчально-методичним забезпеченням.

According to the results of the analysis of scientific-methodical literature, the members of the scientific research group found that the topical issue of the application of modern high-functioning systems, as well as fitness technologies in the professional activity of trainers who specialize in martial arts – is devoted to an insufficient number of scientific works. This emphasizes the relevance, timeliness and practical component of the chosen direction of scientific research. The main goal of the study is to develop a program for the formation of theoretical knowledge of trainers who specialize in martial arts in the direction of their application of modern fitness technologies in professional activities. As a result of the study, the members of the research group developed an experimental program for the formation of theoretical knowledge of trainers who specialize in martial arts in the direction of their application of modern fitness technologies in professional activities. The "experimental program" proposed by us is planned to be implemented during 2 main stages: "Formative" and "Basic", with appropriate educational and methodological support and an algorithm for organizing the system of self-education (improvement of qualifications) of representatives of the studied category. Prospects for further research in the chosen field of scientific research include the approbation of an experimental program for the formation of theoretical knowledge of trainers who specialize in martial arts in the direction of their application of modern fitness technologies in professional activities.

Разработана экспериментальная программа формирования теоретических знаний тренеров, специализирующихся в единоборствах в направлении применения ими современных фитнес-технологий в профессиональной деятельности. Предлагаемую «экспериментальную программу» планируется реализовать в течение двух основных этапов: «Формирующего» и «Базового» с соответствующим учебно-методическим обеспечением.
Improving the Theoretical Preparation of trainers who Specialize in Martial Arts for the use of Modern Fitness-technologies in Professional activities
Keywords: багаторічна підготовка; many years of training; многолетняя подготовка; тренери; coaches; тренеры; одноборства; single combat; единоборства; фітнес-технології; fitness technologies; фитнес-технологии; підвищення кваліфікації; certification training; повышение квалификации; професійна компетентність; professional competence; профессиональная компетентность